Transdermal Permeation of Acyclovir by Iontophoresis Technique - Kumaravelrajan, R. (Asian Journal of Pharmaceutics (AJP), 2017)
Context: The approach for improving transdermal drug delivery is a technique called iontophoresis, a promising technology that has already received regulatory approval. Aims: The aim of the present investigation was to develop acyclovir (ACV) gel, which deliver drug through iontophoresis. Formulation variable was drug loading, current density, and hydrogen-ion concentration (pH). Factorial design was used to study the above variable with drug release at T95% as the response variable. Settings and Design: 23 factorial design was used to study the effect of pH, drug loading, and current density as independent variables, to T 95 % of drug release as dependent variables. Materials and Methods: The current settings were maintained at 0.5 mA. The silver wire was connected as anode at one side and silver chloride as cathode at other side. The resistor was fixed to control the flow of current from the equipment. ACV gel was prepared using Carbopol 934P. Ex vivo permeation study was conducted for 6 h in Franz diffusion cell using rat skin. Optimized formulation was analyzed for viscosity, flux, and in vivo animal study. Statistical Analysis Used: Numerical optimization carried out to find out the constrain variables. Contour plot and response surface were also studied for optimized one. Results: Two factorial interaction of independent variable with respect to dependent variable was analyzed by the kinetics of drug release. It was found that the drug release was controlled up to 6 h when variables used as pH 7.4, current input 0.5 mA, and drug loading 5% in the formulation. The Cmax and Tmax of in vivo study revealed 190 ng/ml at 6 h. Conclusions: It was found that the effectiveness of iontophoretic delivery from gel was largely affected by polarity and current density than drug loading. The optimized formulation gave desired release profile up to 6 h. Drug release kinetics seemed to be Korsmeyer-Peppas model (n = 0.875). Further in vivo study in animal model revealed the Cmax and Tmax reached the predicted time of delivery of drug without fluctuation in the plasma level.